Rapid isolation and characterization of Wharton's jelly-derived mesenchymal stem cells maintained in fresh-prepared human AB-serum - Yudy Tjahjono; Sianty Dewi; Bernadette Dian Novita; Hendy Wijaya; Brilliant Dwi Putra; Suryo Kuncorojakti; Lucia Hendriati; FX Himawan Haryanto Jong; Teguh Widodo; Franklin Vincentius Malonda (Universa Medicina)
Background